The Case for Prescribing Metformin Off-Label for a Child in Remission from Ependymoma - Hahn, Emily S. (The Hastings Center report, 2026)
Pediatrics often faces ethical challenges when families request unproven therapies. We respond to a clinical case described in “A Parental Request for an Unproven Treatment for a Rare Pediatric Cancer: Sound Reasons for Not Going Off-Label,” by Margot Hedlin and Louis Voigt, in the same issue of this journal. The case concerns Natalie, a three-year-old in remission from ependymoma, whose parents requested metformin to prevent recurrence. Although Natalie's neuro-oncologist opposed the use of the drug, its favorable safety profile, pediatric Food and Drug Administration approval for other indications, emerging evidence in cancer research, and endorsement by a specialist support careful consideration. Off-label prescribing is common in pediatric oncology due to issues presented by rare diseases and due to the limitations of clinical trials. With informed consent, monitoring, and interdisciplinary input about the patient's care, prescribing metformin may be ethically justifiable despite uncertain efficacy. This case illustrates the balance between evidence-based practice, patient- and family-centered care, and the realities of pediatric cancer treatment.